Cyclic Behavior of Beam-Column Connections in Precast Structures - Meydanli Atalay, Hilal; Ozden, Sevket (Frontiers in Built Environment, 2021)
The performance of precast concrete structures is greatly influenced by the response of beam–to-column connections. In this study, a new moment resisting precast concrete beam-column connection detail with post-tensioning bolts, made out of high yield strength spring steel, has been experimentally investigated as an alternative to the conventional precast moment resisting connections. Precast specimens and an aseismic monolithic reference specimen have been tested under reverse cycling loads. The contribution of the mild steel in the connection region to the flexural moment capacity, and to the initial pre-stressing force on post-tensioning bolt have been the main test variables. The moment capacity, stiffness, energy dissipation capacity and the residual displacement performance of the precast connections have been compared with those of the aseismically detailed monolithic connection. The conducted tests reveal that the connection detail with steel corbel along with the post-tensioning bolt and mild steel has superior performance properties as compared to the companion precast specimens.